Patterns of physical activity and dietary habits among adolescents in Saudi Arabia: A systematic review - Alasqah, Ibrahim; Mahmud, Ilias; East, Leah; Usher, Kim (International Journal of Health Sciences, 2021)
Objective: Physical inactivity and unhealthy dietary habits are behavioural risk factors associated with non-communicable diseases. The current study aimed to determine the prevalence of physical activity and dietary habits among adolescents in Saudi Arabia. Methods: A systematic electronic literature search of PubMed, SCOPUS, Web of Science, and BIOSIS was conducted through April 2018 using the following keywords: (physical activity OR physical inactivity OR diet OR dietary habits) AND Saudi Arabia. Extracted data from each study were tabulated, and data were synthesised narratively. Results: Eighteen studies published within 2007-2017 were included in the narrative synthesis. The prevalence of physical activity among adolescents in Saudi Arabia ranged from 4% to 44.5%. Fast foods consumption, skipping breakfast, and low fruit and vegetable consumption were the most reported unhealthy dietary habits. Conclusion: Our review highlights that physical inactivity and unhealthy dietary habits were high among adolescents in Saudi Arabia. These findings require immediate actions and plans to increase levels of physical activity and healthy dietary habits among Saudi adolescents.